Dielectric, ferroelectric, and energy storage properties of Ba(Zn1/3Nb2/3)O3-modfied BiFeO3–BaTiO3 Pb-Free relaxor ferroelectric ceramics. Issue 3 (1st February 2021) - Tang, Mingyang; Yu, Linjiang; Wang, Yifei; Lv, Jingwen; Dong, Jia; Guo, Biao; Chen, Fukang; Ai, Qiao; Luo, Yu; Li, Quan; Yu, Kun; Wu, Fei; et al.
Abstract: Pb-free bulk ceramics (1- x )[0.65BiFeO3 -0.35BaTiO3 ]- x Ba(Zn1/3 Nb2/3 )O3 were produced by traditional solid-state reaction route. In this experiment, Ba(Zn1/3 Nb2/3 )O3 (BZN) was introduced to destroy long-range order domains in order to obtain higher energy storage performance. Impedance and XPS analysis indicate that oxygen vacancies exist and participate in relaxation processes at high temperatures. With the increase of BZN content, the dielectric relaxation behavior is improved, the hysteresis loop becomes thinner, remnant polarization decreases, and the breakdown electric field increases to 180 kV/cm in 15BZN. A maximum W rec (1.62 J/cm 3 ) is eventually reached in 7BZN with great temperature stability. The highest efficiency is 91% in 15BZN with W rec of 1.28 J/cm 3 . Charge-discharge tests show that ceramics have a quick discharge time of t 0.9 < 0.1 μs, which makes BZN-doped ceramics a potential candidate for energy storage devices.